Combined exercise and Hawthorn protect against learning impairments and hippocampal damage from trimethyltin neurotoxicity in rat - Maryam Keshvari; Ali Heidarianpour; Farzaneh Chehelcheraghi (Scientific Reports)
Abstract Hawthorn is used to treat various diseases in traditional medicine. Hawthorn active compounds have anti-inflammatory and neuroprotective effects. Considering the few studies, we investigated exercise training different models along with hawthorn oral consumption on the negative changes created in the hippocampus tissue of rats with neurotoxicity caused by Trimethyltin (TMT). Neurotoxicity was induced by TMT intraperitoneal injection. 2-weeks after the injection and confirmation of disease, the Endurance, Resistance, Combined training protocols and hawthorn oral consumption were implemented for 12-weeks. To evaluate learning and spatial memory, the Morris water maze test and Reverse test was performed in the 12th week. We examined the expression of BDNF/Trk-β proteins in the hippocampal tissue in order to confirm or disconfirm the neurogenesis-related learning and memory test. Following the increased of β-Amyloid plaques, acetylcholinesterase activity, inflammation, and decreased antioxidants levels in the hippocampus of neurotoxic rats, the BDNF/Trk-β proteins expression decreased and adverse tissue changes and a great disorder Neurogenesis-dependent spatial learning and memory were observed. 12-weeks of combined training with hawthorn, a good adjustment had in all measured functional and molecular variables. Eosinophilic neuronal necrosis reduction, Astrogliosis reduction, increased Presumable synaptic incrustation and increased Microgliosis were observed in the hippocampal tissue of rats in the TMT + Combined + Hawthorn group. The superiority of the endurance and resistance training combination with hawthorn oral consumption than the unit implementation of these interventions was achieved in reducing the negative changes in the structure and the hippocampus function of neurotoxicity rats through increasing the neurotrophins levels and cholinergic modulation.